Song and silence : ethnic revival on China's southwest borders - Davis, Sara L. M. (Sara Leila Margaret), 1967- (Columbia University Press, 2005)
In the sunny, subtropical Sipsongpanna region, Tai Lues perform flirtatious, exoticized dances for an increasingly growing tourist trade. Endorsed by Chinese officials, who view the Tai Lues as a?model minority," these staged performances are part of a carefully sanctioned ethnic policy. However, behind the scenes and away from the eyes and ears of tourists and the Chinese government, a different kind of cultural resurgence is taking place. In this vivid and beautifully told ethnography, Sara L.M. Davis reveals how Tai Lues are reviving and reinventing their culture in ways that.